Optimal Electricity Allocation Model Under China's Planning-Market Double-Track Mechanism Considering Bidding Game of Generation Companies - Cui, Jinrui; Li, Yating; He, Chuan; Zhang, Zhi; Wang, Haichao; Tang, Jiajun; Li, Yongbo; Cai, Hualin; Lin, Zhenzhi; Yang, Li (Frontiers in Energy Research, 2021)
Under the planning-market double-track mechanism on generation side implemented in China, unreasonable market-oriented power generation proportion may lead to unnecessary vicious competition and market price changes, which is against the will of the power exchange (PX). Given this background, a bi-level model of planning-market electricity allocation considering the bidding game of generation companies is proposed for the smooth transition of power system reform in this paper. In the upper-level model, the proportion of planned electricity is optimized by PX to minimize the average social electricity purchasing price. In the lower-level model, with the impact of market power on the bidding strategy of generation companies considered, the bidding strategy of the generation company set as the price-maker is proposed by using the re-sidual demand curve analysis method, while the price-takers adopt the lowest bidding strategy. Simulations based on data from a provincial electricity market in China illustrate that the pro-posed model can effectively reflect the impact of market-oriented electricity proportion on market power and market clearing price, thus providing a quantitative basis for PX to determine the proportion of market-oriented electricity in total electricity consumption.